"In vivo" digestibility and delayed forage consumption of Digitaria eriantha Stend and Bothriochloa intermedia (R. Brown) Camus (Semiárida, 2020)
The present work is an evaluation of Digitaria eriantha and Botriochloa intermedia deferred forage, through the following parameters: "ln vivo" digestability (D), dry matter intake (DMI), digestible dry matter intake (DDMI), selectivity, plant structure (stem leaf fragment) and the contribution of their nutritive components to the diet. A trial has been conducted following two treatments, one per specie, using five Corriedale lambs in each one of them, showing as a result no significant differences between both groups' weight. "In vivo" digestibility was accomplished by the total excrements collection method during eight days for Digitaria eriantha and 7,5 days for Bothriochloa intermedia. After a seven-day-period to habituate animals to the diet. The forage was offered "ad libitum" by halves, time agreed on: in the morning and afternoon, after excrements were collected. Digestibility resulted for Digitaria eriantha and Bothriochloa intermedia: 52,04 % and 45,92 %; DMI: 66,70 g/kgPV0,75 and 46,54 g/kgPV0,75; DDMI: 34,69 g/kgPv0,75 and 21,35 g/kgPV0,75, respectively. For these three parameters measured, differences between species were highly significant (P< 0,01). In order to compare the results obtained with sheep with those of bovine according to the formula developed by Playne (1978), digestibility and DOMI have been corrected for both Digitaria eriantha and Bothriochloa intermedia with the following result: 55,32 %, 51,20 % and 36,88 g/kgPV0,75, 23,82 g/kgpv0,75, respectively. Larger result values than those corresponding to warm season species actually spread out in this region. In the case of Digitaria eriantha, it surpassed the maintenance level for a L.W. 400 kg cow. Selectivity did not show remarkable differences. The nutritive composition resulted different (P< 0,01); Bothriochloa intermedia showed greater values of wall cell, lignin and ashes, while Digitaria eriantha had more crude protein. There weren't statistic differences in wall cell digestibility. The differences between both deferred species were mainly centered in the different canopy structure. Bothriochloa intermedia drops most of its leaves, offering a high proportion of stem (82 % of stem and 18 % of leaf) while Digitaria eriantha keeps it almost totally (47 % of stem and 53 % of leaf). Therefore, the greater the leaf participated in the Digitaria eriantha diet the better the quality obtained (cell's contents) and the greater intake.
Keywords: intale; deferred forage; Digitaria Eriantha; Bothriochloa intermedia